Operational Risk Analysis (Case Study At Pt Wsb) (GEMA EKONOMI, 2022)
The purpose of this study is to identify and understand the operational risks that occur at PT WBS. The analytical method used in this final project is a qualitative method with data collection techniques in the form of interviews, direct observation, and literature study. This analysis was carried out using Enterprise Risk Management (ERM) analysis. The steps taken in conducting the analysis are identifying risks, determining risk priorities, determining the form of response to risks, implementing responses, and developing a risk monitoring system. The results obtained are that PT WBS has 12 operational risks that may occur, namely the risk of human resources, processes, information, materials, machines, and external factors. The risk with the highest risk scoring result is the M2 risk, namely system error, and how to respond to it by reducing the risk. Other risks are responded to based on their level. This research focuses on risk with medium, high and medium levels. At the medium, high and medium levels, the response was reduction, the low medium level was responded to by reduction, monitoring was carried out, and at the low level the risk response was to accept the risk with regular monitoring